Utilization of Emerging Technologies for Improved Service Delivery in Public University Libraries in Rivers State, Nigeria - Ukaegbu, Bernadette C. N.; Okwu, Emmanuel (Ghana Library Journal, 2022)
This study investigated the utilisation of emerging technologies for improved service delivery in public university libraries in Rivers State. Two research questions guided the study. The research questions were to identify the emerging technologies in use for improved service delivery among public university information professionals in Rivers State and to find out the extent to which information professionals utilized emerging technologies for improved service delivery in public university libraries in Rivers State. The population consists of 50 information professionals in the three universities; University of Port Harcourt (20), Rivers State University (19) and Ignatius Ajuru University of Education (11) respectively. A sample size of 50 information professionals in the universities representing 100% of the population served as respondents. An accidental sampling technique was used for the study. All the information professionals that make up the population were used. A 12-item questionnaire was used for data collection. Cronbach alpha statistics was used to obtain the 0.77 reliability coefficient of the instrument. Mean scores and standard deviation were used to answer the research questions while the z-test statistics were used to test the hypotheses at a 0.05 level of significance. The result amongst others revealed that social network websites technologies and video-based communication platforms like the Zoom and WebEx are in use in both Federal and State library but digital reference robots, library automation SOUL software and Protocols VoIP (Voice over Internet) was not in use in both Federal and State university libraries. It was recommended that university management should give the required attention to library use, provide and encourage the application of digital reference robots, library automation SOUL software and Voice over Internet Protocols (VoIP) and other current gadgets to be used to meet the demand of library users, most especially at this period of post covid-19 pandemic.